Macroeconomic Imbalances in the EU - Stefan Ederer; Peter Reschenhofer (WWWforEurope, 2013)
This paper aims to identify different growth patterns in the EU which led to the emergence of macroeconomic imbalances. It provides a detailed statistical picture of the evolution of various macroeconomic variables on the demand as well as on the supply side, before, in and after the financial and economic crisis of 2008/09. It investigates the causes and discusses various 'channels' which led to macroeconomic imbalances by means of a descriptive analysis of the key determinants of macroeconomic developments, such as wage and price developments, productivity growth etc. Special emphasis is given to developments of the share of labour in national income, the real interest rate and the real exchange rate. The analysis of this data set provides a comprehensive picture of the underlying causes for the specific growth patterns as well as a first assessment of their role in the development of macroeconomic imbalances within the EU. It derives tentative conclusions as to how macroeconomic imbalances can arise in a monetary union and how they can be addressed properly by economic policy.
Keywords: E61; F41; 330; EU integration; European economic policy; European governance; European Monetary Union; Macroeconomic disequilibria